193k views
2 votes
What is 6(1+3m)=-8-2m+5)-4

User Jobelle
by
6.2k points

1 Answer

7 votes

Answer:

m = (-13)/20

Explanation:

Solve for m:

6 (3 m + 1) = -2 m - 8 - 4 + 5

Grouping like terms, -2 m - 8 - 4 + 5 = -2 m + (-8 + 5 - 4):

6 (3 m + 1) = -2 m + (-8 + 5 - 4)

-8 + 5 - 4 = -7:

6 (3 m + 1) = -7 - 2 m

Expand out terms of the left hand side:

18 m + 6 = -2 m - 7

Add 2 m to both sides:

18 m + 2 m + 6 = (2 m - 2 m) - 7

2 m - 2 m = 0:

18 m + 2 m + 6 = -7

18 m + 2 m = 20 m:

20 m + 6 = -7

Subtract 6 from both sides:

20 m + (6 - 6) = -6 - 7

6 - 6 = 0:

20 m = -6 - 7

-6 - 7 = -13:

20 m = -13

Divide both sides of 20 m = -13 by 20:

(20 m)/20 = (-13)/20

20/20 = 1:

Answer: m = (-13)/20

User ZiGaelle
by
5.4k points